Advanced Self-Healing Polymer Composites for Wind Turbine Blades - (:unkn) unknown (My University, 2016)
Wind energy is one of the prime sources of energy among the renewable sources of energy. Wind power has been one of the most promising sources of long-term, clean energy. Materials and design approach in commercial wind turbines have not seen a momentous change in the recent years. In this study, an intriguing bio-mimetic design approach is sought after, which is to heal damages as they arise in a composite material. Self-healing material systems in wind turbine blades have the potential to fulfill the requirement as an added safety mechanism to heal damages and prevent catastrophic failures. Effectively supplying healing agent throughout the composite structure without degrading essential properties is of core interest in this study. Several cost efficient and straightforward techniques to produce vascular channels are attempted in this study. Millimeter and micro scale Borosilicate tubes are used to store and supply the healing agent in glass fiber reinforced thermoset polymer composites with an effort to strengthen and retain the mechanical properties of the composite material. Tensile and bending tests are performed to compare the mechanical properties of polymer composites with tubes to that of without-tubes composite material. Also, Glass transition temperature, the effect of fiber orientation and effect of vacuum infusion process on a conventional composite material (without tubes) were studied. An attempt was also made to mold and test for mechanical properties of a woven fiberglass reinforced thermoplastic polymer composite material. Wind turbine blades are under continuous bending forces, and hence, the self-healing of woven fiberglass reinforced thermoset composite material was demonstrated using three-point bending tests. An Ultra Violet (UV) light sensitive dye was mixed with the healing agent to observe the breakage of vascular Borosilicate tubes (500μm outer diameter) and flow of healing agent into the cracks during the bending tests. The flow of healing agent during the flexural test clearly demonstrated discharge of healing agent at the damage site, flow of the healing agent into material cracks and spreading of the healing agent throughout the thickness of the composite at the damage site. A minimum average of 84% healing of maximum flexural strength under three-point bending was obtained among three different vascular channel layouts in the composite material. A prototype of a wind turbine with self-healing Borosilicate vascular tubes embedded in woven fiberglass reinforced thermoset composite blade was also fabricated and tested in a wind tunnel. Depletion of healing agent within the tubes after wind tunnel testing verified the usefulness and potential for self-healing in future wind turbine blades.